Analysis Of The Urgency Of Proving Predicate Crime In Money Laundering Cases(Predicate Crime: Human Trafficking Crime) - Kirana Ardhelia Putri; Bambang Waluyo (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2024)
Not all crimes use the same evidentiary system, one of which is Money Laundering which uses a reverse evidentiary system and does not require proof of the predicate crime. Proving the predicate crime of Human Trafficking contradicts Article 69, as well as how the evidentiary mechanism in court creates legal uncertainty. The method used is the normative legal research method, with the technique or method of data collection used being library research. The results of this study are that there must be changes regarding the mechanism of proving TPPU, especially in establishing its predicate crime. In the trial process, of course, there is no need to wait until the proof of the predicate crime is completed and decided. The trial process for TPPU cases can still be carried out but does not set aside the tracing and proving of the predicate crime. Proving the predicate crime can also analyze various other financial flows, which cannot be proven or are missed in the proof of the TPPU case. Without proof, it will lead to misuse of Article 69 of Law Number 8 of 2010. The government should be able to change or revoke Article 69 of Law Number 8 of 2010 because it is often misinterpreted by law enforcement officers and used as a loophole by suspects.